Application of Trichoderma harzianum T10 Liquid Formula Based On Soybean Flour Against Cucumber Seedlings Damping-Off (Pythium sp.) - Soesanto, Lukas (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2020)
ABSTRACTProper concentration of soybean flour in the liquid formulation for Trichoderma harzianum T10 growth, its influence to suppress damping-off, and on the growth of cucumber seedlings was investigated. Randomized completely design was used in in vitro test with five treatments and five replicates. The treatments were T. harzianum T10 in Potato Dextrose Broth (control), T. harzianum T10 in soybean fluor of 1, 2, 3 and 4%. Randomiszed block design was used in in planta test with six treatments and five replicates. The treatments consisted of control, T. harzianum T10 in Potato Dextrose Broth, T. harzianum T10 in soybean fluor of 1, 2, 3, and 4%. Variables observed were conidia density, incubation period, disease incidence, area under the disease progress curve, maximum potentially growth, germination persentage, crop height, root fresh weight, shoot fresh weight, and root length. Result of the research showed that the right liquid formulation for T. harzianum T10 growth was the use of soybean fluor with concentration of 2% resulting conidia density as 67,10% compared to PDB. The formulation could suppress the disease incidence, decrease AUDPC value, increase root wet weight, crown wet weight, and root length as 66.67, 66.10, 57.36, 43.81, and 41.81%, respectively, compared to control. Keyword: cucumber, damping-off, liquid formula, soybean flour, Trichoderma harzianum